Karakteristik Orang-orang Munafik dalam Surat Al-Munafiqun (Studi Tafsir Ibnu Katsir) - Sulton, Ghofari; Sulthoni, Akhmad; Parwanto (Hamalatul Qur'an : Jurnal Ilmu Ilmu Alqur'an, 2024)
In the Qur'an there is a classification of humans based on their aqidah in three groups: believers, disbelievers, and hypocrites. The hypocrites are those who believe in Allah and the Last Day, but their faith is only in their mouths, while their hearts disbelieve. This research is a literature research with an analytical descriptive approach. The primary data source is Tafsir Al-Qur'an Al-Azhim by Ibn Katsir. While secondary data is the book of tafsir and other books that have relevance to the discussion of this research. This research uses documentation method and maudhu'I or thematic as data analysis technique. Ibn Katsir interpretation of Surah Al-Munafiqun is that hypocrites have an attractive appearance, but their hearts are full of hatred for Allah, rejecting advice, and Allah confirms that they will get curse, and delaying good deeds is a characteristic of hypocrites. Allah, the Almighty, explains that the characteristics of hypocrites in Surah Al-Munafiqun include disbelief and hatred of the truth, instability in faith, inclination towards lies and falsehood, laziness and indifference towards obedience, fear in practicing religion, and indifference towards the guidance of Allah, the Almighty.